Revealing the Secrets of Mubarak Clinic's Success: A Success Story in Undergoing Accreditation Surveys (Case Study) - Wahyudi, Ahyar; Nurhikmah (Asian Journal of Healthcare Analytics, 2023)
Accreditation, which is defined as the process of quality evaluation by an independent institution based on a set of established standards, is granted to Mubarak Clinic by the Indonesia Healthcare Facility Accreditation Agency or Lembaga Akreditasi Fasilitas Kesehatan Indonesia (LAFKI). The research method used is a case study, as a form of qualitative research, not focusing on the quantity of acquired data but based on the quality of the obtained data. Mubarak Clinic has demonstrated excellence in several areas, but there is room for improvement, especially in human resource management, facility management, and patient safety procedures. By focusing efforts on areas that need improvement, Mubarak Clinic can continue to enhance the quality and safety of patient care.